Development of an ethnomathematics-based e-module on the dori mpulor traditional house to enhance students' mathematical problem-solving ability - Ellissi, Wike; Liliana, Sepriani (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study was motivated by the low performance of Indonesian students in mathematics, as reflected in the 2022 PISA results, which indicated that Indonesia’s average mathematics achievement remained below the OECD average. This condition shows the need for learning materials that can support students’ conceptual understanding and mathematical problem-solving ability through contextual and meaningful learning. This study aims to develop an ethnomathematics-based e-module on the Dori Mpulor traditional house to enhance students’ mathematical problem-solving ability. The research employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 85 junior high school students from three schools in Landak, Sanggau, and Sekadau Regencies. Data were collected through observation, questionnaires, interviews, and mathematical problem-solving tests. The quality of the e-module was assessed based on validity, practicality, and effectiveness. The results showed that the e-module obtained an average validity score of 92.55%, categorized as very valid, and an average practicality score of 90.90%, categorized as very practical. The effectiveness test produced an N-Gain score of 0.76, categorized as high. These findings indicate that the ethnomathematics-based e-module on the Dori Mpulor traditional house is valid, practical, and effective in enhancing students’ mathematical problem-solving ability. The e-module also provides contextual learning experiences by connecting formal mathematical concepts with local cultural values.